Pharmacogenetics and analgesic effects of antidepressants in chronic pain management. (March 2015) - Rodieux, Frédérique; Piguet, Valérie; Berney, Patricia; Desmeules, Jules; Besson, Marie
Antidepressants are widely administered to chronic pain patients, but there is large interindividual variability in their efficacy and adverse effect rates that may be attributed to genetic factors. Studies have attempted to determine the impact of genetic polymorphisms in enzymes and transporters that are involved in antidepressant pharmacokinetics, for example, cytochrome P450 and P-gp. The impacts of genetic polymorphisms in the targets of antidepressants, such as the serotonin receptor or transporter, the noradrenaline transporter and the COMT and monoamine oxydase enzymes, have also been described. This manuscript discusses the current knowledge of the influence of genetic factors on the plasma concentrations, efficacy and adverse effects of the major antidepressants used in pain management.